2019
DOI: 10.25259/jgoh-7-2018
|View full text |Cite
|
Sign up to set email alerts
|

Association of dental anxiety with personality traits among Al Azhar arts students in Thodupuzha, Kerala

Abstract: Introduction: Dental anxiety remains a barrier to dental care for a considerable proportion of the population. The psychological profile of patients dentally anxious but not highly anxious is quite similar to normal (non-anxious) patients’ profile. Aims and Objectives: The aim of the study is to assess personality traits and prevalence of dental anxiety and to find an association between dental anxiety and personality traits in arts students. Materials and Methods: A cross-sectional study was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Firstly, the results represented a single-center experience and were obtained from a small population size. Moreover, dental anxiety in children is multifactorial, and this research did not explore the effect of personal traits and family-related issues, including socioeconomic status and level of education of caregivers [40,41,[58][59][60]. Moreover, transforming the Faces Anxiety Scale into the Likert scale allowed for a more in-depth statistical elaboration of the results, although the study was not designed to delve into explaining the exact reasons for the observed anxiety levels in children.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the results represented a single-center experience and were obtained from a small population size. Moreover, dental anxiety in children is multifactorial, and this research did not explore the effect of personal traits and family-related issues, including socioeconomic status and level of education of caregivers [40,41,[58][59][60]. Moreover, transforming the Faces Anxiety Scale into the Likert scale allowed for a more in-depth statistical elaboration of the results, although the study was not designed to delve into explaining the exact reasons for the observed anxiety levels in children.…”
Section: Discussionmentioning
confidence: 99%